2008
DOI: 10.1186/1471-2458-8-219
|View full text |Cite
|
Sign up to set email alerts
|

The 10/66 Dementia Research Group's fully operationalised DSM-IV dementia computerized diagnostic algorithm, compared with the 10/66 dementia algorithm and a clinician diagnosis: a population validation study

Abstract: Background: The criterion for dementia implicit in DSM-IV is widely used in research but not fully operationalised. The 10/66 Dementia Research Group sought to do this using assessments from their one phase dementia diagnostic research interview, and to validate the resulting algorithm in a population-based study in Cuba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 116 publications
(155 citation statements)
references
References 17 publications
4
146
0
5
Order By: Relevance
“…On the other hand, prevalence may have been underestimated by studies that did use the specific protocol. This latter hypothesis is not substantiated, however, because studies have shown that prevalences tend to be lower when obtained using conventional diagnostic methods than when using the adapted protocol [33,34]. In the present study, diagnostic assessment protocols adapted for low educational level were not used, but the difficulties stemming from illiteracy and low education are believed to have been reduced, because unlike other Brazilian studies the study population comprised mainly individuals with substantial schooling.…”
Section: Discussionmentioning
confidence: 39%
“…On the other hand, prevalence may have been underestimated by studies that did use the specific protocol. This latter hypothesis is not substantiated, however, because studies have shown that prevalences tend to be lower when obtained using conventional diagnostic methods than when using the adapted protocol [33,34]. In the present study, diagnostic assessment protocols adapted for low educational level were not used, but the difficulties stemming from illiteracy and low education are believed to have been reduced, because unlike other Brazilian studies the study population comprised mainly individuals with substantial schooling.…”
Section: Discussionmentioning
confidence: 39%
“…32 Current diagnostic criteria define a 'narrow category of unambiguous dementia characterised by marked impairment'. 46 The limitations of the current DSM IV-TR diagnostic system has the potential to under-estimate the prevalence of dementia with significant socio-clinical implications. 47 Similar diagnostic challenges are encountered with MCI diagnosis.…”
Section: Prevalence Of Dementia and MCImentioning
confidence: 99%
“…En la categoría de deterioro cognitivo se incluyeron los casos identificados como deterioro cognitivo leve o demencia. El deterioro cognitivo leve lo definimos de acuerdo con los criterios de la Clínica Mayo para deterioro cognitivo leve amnésico, operacionalizados mediante un algoritmo desarrollado por el GID 10/66 18 ; la demencia, según la presencia de síndrome demencial, definida a partir de los criterios del DSM-IV y del algoritmo también desarrollado por el GID 10/66, mismos que han sido validados en población de ingreso económico medio o bajo 19 y en estudios poblacionales teniendo el juicio clínico como método de referencia 20 . -Antecedentes personales de depresión: documentada mediante el reporte de historia personal de depresión, vacío o tristeza que hubiera afectado sus actividades de la vida diaria, con duración de al menos 2 semanas.…”
Section: Variable Dependienteunclassified